Pengaruh Motivasi Kerja Dan Gaya Kepemimpinan Demokratis Terhadap Kinerja Pegawai PT. Bank BRI KC Malang - Muchammad Ar-Rony Septianda; Budi Wahono; Khalikussabir Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study aims to determine the extent to which the influence of work motivation and democratic leadeship style on employee performance at PT Bank BRI. The population in this study were 135 employees and the sample used in this study used IBM SPSS version 25. The results obtained were that Work Motivation and Democratic Leadership Style had a positive and significant concurrent effect on the performance of PT Bank BRI employees, while partially work motivation had a positive and significant effect on employee performance at PT Bank BRI, democratic leadership style has a positive and significant effect on the performance of PT Bank BRI employees. Keywords: Work Motivation, Democratic Leadership Style, Employee Performance.